External Capital Structures and Oil Price Volatility - John D. Burger; Alessandro Rebucci; Francis E. Warnock; Veronica Cacdac Warnock (Inter-American Development Bank (IDB), 2010)
This paper assesses the extent to which a countrys external capital structure can aid in mitigating the macroeconomic impact of oil price shocks. Two Caribbean economies highly vulnerable to oil price shocks are considered: an oil importer (Jamaica) and an oil exporter (Trinidad and Tobago). From a risk-sharing perspective, a desirable external capital structure is one that, through international capital gains and losses, helps offset responses of the current account balance to external shocks. It is found that both countries could alter their international portfolio to provide a better buffer against such shocks.
Keywords: F3; G1; 330; Hedging; Oil; Foreign assets and liabilities; International portfolios